Research portfolio - Daphney, Robert (Rhodes University, Faculty of Education, Department of Education, 2001)
This portfolio of work represents three research projects on issues related to teacher education. The research was undertaken at Dr. W.B. Rubusana College of Education over a period of three years. The first project is a situational analysis that attempts to determine whether the college is capable of meeting the challenges placed on it by the evolving South African Educational System. The key finding is that the college is not ready to embark on the changes required by the Ministry of Education chiefly because its educators and learners are seemingly not ready to embrace change. The second project is a case study that attempts to determine whether a group of 12 Senior Primary students at the college are able to interpret photographs of the local environment and as such provide evidence of their ability to be environmental educators through the medium of geography. The findings indicate that they are only able to read the photographs at a very superficial level. Their poor communication skills and their disadvantaged backgrounds seem to prevent them from achieving the level of thinking required for them to be effective environmental educators. The third project describes, analyses and evaluates a fieldwork study done with a class of Senior Primary students at the college. While the students did not achieve the necessary progression from 'look and see' to 'enquiry based' fieldwork the project was valuable in that it was an educative experience for both teacher and learner and provides evidence of the value of action research and reflective teaching.
Keywords: Teachers colleges -- South Africa -- Eastern Cape; Competency-based education -- South Africa -- Eastern Cape; Geography -- Curricula; Geography -- Fieldwork -- Study and teaching; Geography -- Study and teaching